The Berau Government's Diplomatic Efforts In The International Promotion of The Derawan Islands Through The Ocean Governance Project In 2022-2023 - Akhrianti, Dinda Nurhaliza; Decreto Ariana, Eagle Deus (Journal of International Relations on Energy Affairs, 2023)
This research examines how the Berau Government's diplomacy efforts in promoting sustainable tourism in the Derawan Islands. This is based on the signing of the Minutes of Agreement by the Berau Government with WWF and EU within the framework of the Ocean Governance Project (OGP) cooperation in 2022. This cooperation includes a series of agendas within the OGP framework, including community and community assistance, coral reef and marine biota conservation, and sustainable tourism development. This research uses the concepts of paradiplomacy and sustainable tourism as an analytical tool. This research is conducted in a descriptive analytical manner based on data derived from official reports of the Berau Government, East Kalimantan Provincial Government, WWF, OGP website, as well as literature sources from previous research on related issues. Based on the analysis, the collaboration carried out by the Berau Government within the OGP framework is a diplomatic effort to promote sustainable tourism in the Derawan Islands at the global level. There are three main steps taken by the Berau Government within the OGP framework to promote sustainable tourism in the Derawan Islands, namely rehabilitation and conservation of marine ecosystems, economic development through the tourism sector, and improving the image of the Derawan Islands as a sustainable tourist destination.